Evaluasi Program Kartu Puan Molek dalam Mengoptimalkan Distribusi LPG 3 Kilogram Bersubsidi di Kota Tanjungpinang - Yulian Jitmau; Yudhanto Satyagraha Adiputra; Eki Darmawan (Perspektif Administrasi Publik dan hukum, 2025)
The scarcity of subsidized 3-kilogram LPG in Tanjungpinang City has become a crucial public issue, primarily due to inaccurate distribution. The Puan Molek Card program was designed as an innovative solution to reorganize the LPG subsidy distribution mechanism to make it more manageable and in favor of poor households and eligible MSMEs. An evaluation based on William Dunn's six dimensions showed that in the initial phase, the program's effectiveness and efficiency were quite high, supported by collaborative data collection between local governments, neighborhood associations (RT/RW), and community social institutions. The card also provided convenient access and reduced the potential for hoarding by irresponsible individuals. However, over time, inconsistent card use and weak oversight caused the program's effectiveness to decline. Many residents returned to using ID cards (KTP) as a substitute, opening new opportunities for distribution irregularities. This indicates that the dimensions of accuracy and accountability have not been maintained sustainably. The study also noted that although LPG distribution was relatively smooth, there is a long-term potential for declining public trust if the government does not immediately implement improvements. Therefore, the main recommendations are strengthening the digital-based monitoring system to record LPG subsidy transactions in real time, as well as integrating the Puan Molek Card with population data to prevent misuse. Furthermore, local governments need to intensify public awareness campaigns on the importance of card use and conduct regular field monitoring. Cross-sector collaboration, including with Pertamina, distribution agents, and independent oversight bodies, is also needed to ensure the program returns to its primary objective: ensuring that the 3-kilogram LPG subsidy reaches those entitled to it.